Isolation of a broad spectrum antibiotic producer bacterium, Pseudoalteromonas piscicida PG-02, from the Persian Gulf (Bangladesh Journal of Pharmacology, 2011)
The aim of this study was to isolation of marine antibiotic-producing bacteria from the Persian Gulf, as an untapped source for searching new natural drugs. Bioactivity of ethyl acetate extract prepared from marine bacterial isolates was evaluated against 21 human pathogenic bacteria. GCI (Growth Curve Interference) parameter was determined for the obtained marine antibiotic compound against MRSA (Methicillin resistant Staphylococcus aureus). Finally, identification of intended isolate was done based on phenotipically and phylogenetically characters. Overall, 49 bacterial colonies were isolated but only one isolate from coastal sediment identified as Pseudoalteromonas piscicida PG-02 showed antibacterial activity. It was effective against all of tested bacteria except Listeria monocytogenes (clinical), L. monocytogenes (ATCC 19112), Proteus mirabilis (clinical) and Klebsiella pneumoniae (clinical). GCI parameter was obtained with concentration just near to MIC (GCI: 20 mg/mL). In conclusion, this marine bacterium can give hopes for treatment of diseases caused by multidrug resistant (MDR) bacteria.